2007
DOI: 10.1002/mrm.21420
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cerebral perfusion using dynamic susceptibility contrast MRI: Evaluation of reproducibility and age‐ and gender‐dependence with fully automatic image postprocessing algorithm

Abstract: A novel approach for quantifying cerebral blood flow (CBF) is proposed that combines the bookend technique of calculating cerebral perfusion with an automatic postprocessing algorithm. The reproducibility of the quantitative CBF (qCBF) measurement in healthy controls (N ‫؍‬ 8) showed a higher intraclass correlation coefficient (ICC) and lower coefficient of variation (COV) when calculated with automatic analysis (ICC/COV ‫؍‬ 0.90/0.09) than when compared to conventional manual analysis (ICC/COV ‫؍‬ 0.58/0.19).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
110
9

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 30 publications
24
110
9
Order By: Relevance
“…Bookend Bland-Altman plots showed larger SDs than in a previous test-retest study by Shin et al [36], who observed an average difference±SD of 1.4±6.9 ml/(min 100g). On the other hand, Crane et al [37] For the Bookend method, the use of GM ROIs resulted in a repeatability that was fairly similar to the previous observations by Shin et al [36].…”
Section: Repeatability Of Gm Cbfcontrasting
confidence: 57%
“…Bookend Bland-Altman plots showed larger SDs than in a previous test-retest study by Shin et al [36], who observed an average difference±SD of 1.4±6.9 ml/(min 100g). On the other hand, Crane et al [37] For the Bookend method, the use of GM ROIs resulted in a repeatability that was fairly similar to the previous observations by Shin et al [36].…”
Section: Repeatability Of Gm Cbfcontrasting
confidence: 57%
“…Previously published studies examining the variability and repeatability of results generated using the bookend technique have reported a testretest intraclass coefficient of 0.90 and coefficient of variation of 0.09. 15,16,20 Potential limitations include differences in WM properties between patients with MS and healthy controls that could theoretically invalidate the bookend assumptions. However, no significant differences were identified between the expected values from the water correction factor model and the observed data points for healthy controls, impaired patients with MS, and nonimpaired patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] These "bookend" scans allow DSC calibration by quantifying parenchymal and blood pool T1 changes while correcting for intrato-extravascular water exchange. 15 The bookend technique does not require normalization for comparative measurements and is reproducible, reliable, 15,16 and accurate compared with PET. 17 The goal of this study was to quantify differences in bookend-derived cerebral perfusion between cognitively impaired and nonimpaired patients with SPMS.…”
mentioning
confidence: 99%
“…The bookend technique has been previously described (12,14,15) but will Dynamic susceptibility contrast (DSC) MR imaging has shown promise in calculating CBF by measuring the susceptibility-induced signal loss with the influx of a contrast agent bolus (7,8). However, due to the inherent complexities of susceptibility imaging, the derived values have only been confirmed to accurately show relative, rather than quantitative, values (7,(9)(10)(11).…”
Section: Bookend Cbf Quantitationmentioning
confidence: 99%